2010
DOI: 10.1159/000287352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron Deprivation on Multidrug Resistance of Leukemic K562 Cells

Abstract: Background and Aim: Multidrug resistance (MDR) compromises the efficacy of chemotherapy. Many approaches have been used to reduce MDR; however, the results are poor. It has been reported that iron deprivation downregulates MDR genes. To investigate the relationship of iron with MDR and early growth response gene-1 (EGR1), we investigated the effect of iron deprivation on expression and/or function of multidrug resistance-1 (MDR1), early growth response gene-1 (EGR1), ferritin heavy chain gene (H-Fn) and MDR1-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…Recent evidence showing that Pgp, a membrane efflux pump involved in the development of the MDR phenotype (Takara et al ., 2006), is induced in tumour cells exposed to 100 µM dexrazoxane (Riganti et al ., 2008) suggests that, by actively extruding doxorubicin and thus lowering its intracellular concentration, Pgp may be a potential mediator of HIF‐dependent cardioprotection. However, we found that Pgp expression was not affected by dexrazoxane in H9c2 cells despite concomitant HIF activation; this discrepancy may be explained by the cell‐specific response of Pgp to iron deprivation, as suggested by a recent study showing Pgp down‐regulation in leukaemic K562 cells exposed to an iron chelator (Fang et al ., 2010).…”
Section: Discussioncontrasting
confidence: 64%
“…Recent evidence showing that Pgp, a membrane efflux pump involved in the development of the MDR phenotype (Takara et al ., 2006), is induced in tumour cells exposed to 100 µM dexrazoxane (Riganti et al ., 2008) suggests that, by actively extruding doxorubicin and thus lowering its intracellular concentration, Pgp may be a potential mediator of HIF‐dependent cardioprotection. However, we found that Pgp expression was not affected by dexrazoxane in H9c2 cells despite concomitant HIF activation; this discrepancy may be explained by the cell‐specific response of Pgp to iron deprivation, as suggested by a recent study showing Pgp down‐regulation in leukaemic K562 cells exposed to an iron chelator (Fang et al ., 2010).…”
Section: Discussioncontrasting
confidence: 64%
“…Some of these studies provide clear evidence about the ability of reduced iron store to accelerate apoptosis, reduce resistance to treatment, and ultimately improve the response to treatment. [ 13 , 31 33 ] Although the present findings are in line with the cited studies, none of them have investigated the role of iron in pediatric ALL. In the present study, regardless of the disease's phenotype, the chances of 3-DFS and response to treatment (by the end of the first year) show a definite reduction with the increase in BMIS.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to its anti‐tumourigenic effects, it was observed that Dp44mT could also be used to overcome multi‐drug resistance (Whitnall et al ., ). These observations are supported by evidence that iron chelators can decrease the expression of multi‐drug resistance genes, including MDR1 (Fang et al ., ).…”
Section: Introductionmentioning
confidence: 97%